“He was a true son of Lowell”: discourse on the opioid epidemic and mortality in a small city - Frederick, Brittany Lee (2020)
This thesis explores the circulating discourse on opioid-related mortality in Lowell, a small, post-industrial city, through analysis of 173 articles from the Lowell Sun from 2007-2017. While opioid-related mortality has been on the rise nationally, the overdose epidemic is concentrated in particular areas, like the Middlesex Valley, a region in northeastern Massachusetts. Unlike the response to previous drug panics, the opioid epidemic has been constructed as a medical problem, that requires rehabilitative treatment rather than punitive intervention. Still, this “gentler” approach has been applied unevenly. This thesis has two main findings. First, the circulating discourse acknowledges the verified diversity of opioid users while simultaneously distancing white middle class men from the stigmatized legacy of the war on drugs in the inner city. This distance from the “urban problem” of drug addiction and possession is reinforced by narratives of the stable, nuclear family, loving mothers, and accidental experimentation with legally prescribed prescription pills. As social panics often mask other problems, in the city of Lowell, anxiety over the mass mortality exists alongside distress about the lack of opportunities for young people despite the city’s revitalization efforts. Second, I demonstrate the plethora of institutional resources available to assist young men struggling from opioid addiction despite the city’s economic problems. In lieu of resources from the state, the city’s residents and organizations adopt neoliberal self-help frames to protect their residents from addiction by providing prevention and treatment resources